Security Analysis of Relay in LTE-Advanced - Hongru Zhu; Minpeng Qi (Dianxin kexue)
The background and the threats of relay were introduced. The security problems about relay node and related security requirements were analyzed. Based on these requirements, some security solutions were made. These solutions can make relay more secure.